TO THE PROBLEM OF INFORMATION AND CREATIVE PROJECTS IN THE ORGANIZATION OF PHYSICAL EDUCATION OF ADOLESCENTS - Necherda , V. В. (НДУ ім. М. Гоголя, 2026)
The purpose of the research is to outline the problem field of project technologies, in particular, information and creative projects in the organization of physical education of modern adolescents. The tasks are to summarize the data of pedagogical theory and practice regarding information and creative projects and to highlight the conceptual provisions of the research. To achieve the purpose of the research, such theoretical methods as a system-structural analysis of domestic and foreign psychological and pedagogical sources concerning the problem of information and creative projects, generalization and comparison of the obtained data were used. The theoretical basis of the research is the conclusions based on the results of scientific research dedicated to the dynamics of the health of Ukrainian adolescents under the influence of the war; provisions that reveal the essence of project technologies, theoretical and practical aspects of their implementation; provisions that reveal the content and structure of information and creative projects. As a result of the study, the author emphasized the methods used in the implementation of information and creative projects in the practice of physical education of modern adolescents, and the educational potential of information and creative projects in the organization of physical education of adolescents, in particular, the activation of adolescents’ reflection processes regarding their own physical development and the necessity for a healthy lifestyle, expanding the base of pupils’ theoretical knowledge regarding the basics of physical culture and the culture of a healthy lifestyle, means of health preservation and health restoration, increasing adolescents’ motivation for physical development and physical activity, promoting their value attitude to their own life and health, self-control and self-education during the hardening of the body, the formation of motor skills and abilities, creating favorable conditions for adolescents to independently and consciously choose their own health preservation models and life position to be physically healthy. The scientific novelty of the research lies in the clarification of the concepts of «project in the organization of physical education of adolescents”, «information projects in the organization of physical education of adolescents» and «creative projects in the organization of physical education of adolescents”. The practical significance of the results obtained lies in the modernization of the system of physical education of adolescents in accordance with social challenges and individual needs.
Keywords: adolescents; physical education; project; information project; creative project; methods